Preparation of tin seleno telluride thin films by potentiostatic and pulse electrodepositon techniques - Chia, Chew Ping (2015)
Deposition of tin seleno telluride thin film on fluorine doped tin oxide (FTO) coated glass was successfully carried out by potentiostatic deposition and pulse electrodeposition methods. The deposition process was done in an acidic bath consisting of Sn-EDTA, Na2SeO3 and TeO2 solutions. Deposition potential was initially determined using cyclic voltammetry (CV), where the CV results indicated that the possible potential range for deposition of tin seleno telluride is between -0.35 V to -0.65 V. In potentiostatic deposition, the effect of deposition potential, annealing temperature,deposition time, bath temperature and bath concentration were studied. Comparison was done based on the results obtained from photoelectrochemical test (PEC) and Xray diffraction (XRD). It was found that tin seleno telluride thin film which was deposited for 40 minutes at -0.40 V in a deposition bath containing 0.010 M Sn-EDTA,0.010 M Na2SeO3 and 0.005 M TeO2 at room temperature exhibited the highest photocurrent and has the good crystallinity. It was also observed that the tin seleno telluride thin film was produced when the sample was annealed at 250 °C. Pulse electrodeposition was carried out for 40 minutes at a potential of -0.40 V vs Ag/AgCl in a solution containing 0.010 M Sn-EDTA, 0.010 M Na2SeO3 and 0.005 M TeO2. The sample was annealed at 250 oC for 30 minutes. The effect of varying duty cycle was studied. PEC and XRD results showed that tin seleno telluride deposited at 50% duty cycle produced a thin film with high crystallinity and good photoresponse. The photocurrent for the thin film deposited using both methods appeared at negative potentials region, revealing the fact that tin seleno telluride is a p-type semiconductor. The XRD results showed that tin seleno telluride (SnSe0.3Te0.7) is polycrystalline with strong cubic structure reflections at (002), (022), (222), (004) and (024) planes. Micrographs obtained from Scanning Electron Microscopy (SEM) showed that the thin film deposited using potentiostatic deposition appeared as non-uniform dendritic crystals where as thin film deposited using pulse electrodeposition appeared as short,rod type loose aggregates at 10 to 50% duty cycle. The thin film obtained from pulse electrodeposition also has better surface coverage compared to the potentiostatic deposition. Data obtained from Energy Dispersive Analysis of X-rays (EDX) revealed that the composition of Sn:Se:Te was 1:5.4:2.8 and 1:7.4:3.5 respectively for both potentiostatic and pulse electrodeposition. The crystallite size of tin seleno telluride obtained from pulse electrodeposition is larger than that from potentiostatic deposition. Optical studies showed that the thin film deposited using both deposition methods have a direct band gap transition with band gap value of 1.60 e V.